PERAN MEDIA CETAK DALAM PENCEGAHAN PORNOGRAFI DI WILAYAH HUKUM KOTA PEKANBARU - Lubis, Fatahillah; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
The Republic of Indonesia is a constitutional state based on Pancasila and the Constitution of 1945 by upholding moral values, ethics, character, and personality of the noble nation, faith, and fear of Almighty God, to respect diversity in social life, nation and the state, as well as protecting the dignity of every citizen. Globalization and the development of science and technology, particularly information and communication technology has contributed to the increase in the manufacturing, distribution, and use of pornography which adversely affected the nations moral and noble personality Indonesia, threatening the life of Indonesian society and social order. Evolving extent of pornography in society also resulted in an increased level of immoral and obscene. Many of the mass media, especially print media daily load things potentially containing pornographic elements in the articles, content and other ads on newspaper editions published. It is actually not in accordance with their role as set out in the legislation. Presentation of the results above, the authors are interested in discussing about Print Media Role In The Prevention Pornography Jurisdiction Pekanbaru.The purpose of this study is to investigate the implementation of the print medias role in the prevention of pornography in the city of Pekanbaru and effort to do the print media in the prevention of pornography in Pekanbaru.This study is a descriptive sociological research, which consists of primary data, secondary and tertiary. Data collection tools such as interviews and literature study. The data have been collected and will be analyzed qualitatively grouped and deductively inferred.Implementation of the print medias role in the prevention of pornography in Pekanbaru City is currently running at max. In its own internal print media, there are no written rules governing the prevention of pornography so that there is no institutional structure that is specifically tasked to prevent pornography so that the implementation of the print medias role in preventing pornography less maximal. The government should pay more attention to the mass media, especially print again circulating today. Because of the authors knowledge in the field, in a story published not have to get permission from the government, only limited requirements for the establishment of PT (Limited Liability Company). This actually increases the possibility of the emergence of the media, especially the print media are not responsible for the regulation ignores the existence of particular Act No. 44 of 2008 on Pornography.